Synthesis, structures, and redox properties of mixed-sandwich complexes of cyclopentadienyl and hydrotris(pyrazolyl)borate ligands with first-row transition metals - Brunker, T; Cowley, A; O'Hare, D (2002)
The synthesis, structures and redox properties of mixed-sandwich complexes of cyclopentadienyl and hydrotris(pyrazolyl)borate ligands with first-row transition metals were studied. Crystal structure determinations were performed for various complexes. Analytical, nuclear magnetic resonance (NMR), infrared radiation (IR) and mass spectroscopic data were consistent with the formulation of the species as mixed-sandwich complexes.